The Metalloproteinase adam19b Is Required for Sensory Axon Guidance in the Hindbrain - Cox, Jane A.; Voigt, Mark M. (Frontiers in Neural Circuits, 2019)
Little is known about the molecular and cellular mechanisms involved in the formation of the cranial peripheral sensory system in vertebrates. In an effort to identify genes involved in the formation of these circuits, we performed a forward genetic screen utilizing a transgenic zebrafish line (p2rx3.2:gfp sl1) that expresses eGFP (green fluorescent protein) in sensory neurons of the Vth, VIIth, IXth and Xth cranial ganglia. In this report, we describe a novel zebrafish mutant in which a missense mutation in the adam19b gene selectively affects the epibranchial sensory circuits.